A socioeconomic and cost benefit analysis of Tropical Race 4 (TR4) prevention methods among banana producers in Colombia. - Thea Ritter; Diego Álvarez; Leslie Estefany Mosquera; Edward Martey; Jonathan Mockshell (PLoS ONE)
The global banana industry faces a significant threat from Fusarium oxysporum f. sp. cubense Tropical Race 4 (TR4). While prior research has concentrated on TR4's dissemination, reproductive conditions, and resistant banana varieties, this study employs a socioeconomic and cost-benefit analysis to explore the vulnerability of banana producers to TR4 in Colombia. It assesses the financial viability of current monitoring strategies and estimates potential losses in the event of TR4 spreading within the study area. Interviews were conducted with producers and key stakeholders in Colombia's top two banana-producing departments, Antioquia and Magdalena. The findings reveal that farming systems are highly vulnerable to TR4, particularly due to the prevalent use of corms. Producers employ preventive measures such as cement paths, fences, disinfecting stations, and footbaths to counteract TR4's spread. A cost-benefit analysis indicates that the benefits of these prevention methods significantly outweigh the associated costs, with a net present value of implementing prevention strategies per hectare of $95,389 USD and $112,527 USD in Magdalena and Antioquia and a benefit-cost ratio of 3.1 and 4.2, respectively. Considering the substantial impact TR4 could have in Colombia if it becomes more widespread, we recommend widespread adoption of preventive measures, including the construction and utilization of cement paths and disinfectant methods on all banana farms. Additionally, to enhance awareness and early detection, we propose leveraging technology, such as mobile applications (apps) and chat groups, to empower farmers in identifying and preventing the spread of TR4.